2021
DOI: 10.1038/s41417-020-00291-4
|View full text |Cite
|
Sign up to set email alerts
|

Roles of miRNA dysregulation in the pathogenesis of multiple myeloma

Abstract: Multiple myeloma (MM) is a malignant disease of plasma cells with complex pathology, causing significant morbidity due to its end-organ destruction. The outcomes of patients with myeloma have significantly improved in the past couple of decades with the introduction of novel agents, such as proteasome inhibitors, immunomodulators, and monoclonal antibodies. However, MM remains incurable and presents considerable individual heterogeneity. MicroRNAs (miRNAs) are short, endogenous noncoding RNAs of 19–22 nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 137 publications
0
39
0
Order By: Relevance
“…The change of miRNA expression level can be used to monitor the progress of multiple myelom, and can also be used as a marker for diagnosis of multiple myeloma. At present, some studies have shown that miRNA-21 is closely related to the occurrence, invasion, metastasis, and drug resistance of tumors, and some studies have taken miRNA as a gene therapy target for multiple myeloma [11][12][13]. Many patients with multiple myeloma have immune dysfunction, and their gene subtypes and chromosomal abnormalities are related to certain miR-NAs, and more than 50% of miRNAs are located in genomic regions such as amplification region, cleavage site, fragile site, and loss of heterozygosity.…”
Section: Introductionmentioning
confidence: 99%
“…The change of miRNA expression level can be used to monitor the progress of multiple myelom, and can also be used as a marker for diagnosis of multiple myeloma. At present, some studies have shown that miRNA-21 is closely related to the occurrence, invasion, metastasis, and drug resistance of tumors, and some studies have taken miRNA as a gene therapy target for multiple myeloma [11][12][13]. Many patients with multiple myeloma have immune dysfunction, and their gene subtypes and chromosomal abnormalities are related to certain miR-NAs, and more than 50% of miRNAs are located in genomic regions such as amplification region, cleavage site, fragile site, and loss of heterozygosity.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma is a haematological malignancy where abnormal expression or dysregulation of miRNAs have been found 127,128 . OIP5‐AS1 has been implicated in the progression of multiple myeloma and the prognosis for multiple myeloma patients via different mechanisms involving miRNAs 7,129 …”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%
“…MM is characterized by the clonal B-cell proliferation in bone marrow typically associated with overproduction of monoclonal proteins that accumulate in serum and urine 2 . The clonal expansion of monotypic plasma cells in the bone marrow is often associated with excessive production/secretion of monoclonal protein into the blood 3 . The development of multiple myeloma causes a variety of clinical symptoms, including anemia, hypercalcemia, immune paresis, and organ damage such as kidney and bone disorders 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma is one of the most common hematological malignancies in adults worldwide and accounts for 1.8% of all cancer cases and approximately 10% of hematologic malignancies 3,4 . In Europe there are more than 48,000 new cases and around 31,000 deaths each year 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation